Mass transfer and solubility of CO and H-2 in ionic liquid. case of [Bmim][PF6] with gas-inducing stirrer reactor - Sharma, Amit; Julcour, Carine; Kelkar, Ashutosh A.; Deshpande, Raj Madhukar; Delmas, Henri (Industrial & Engineering Chemistry Research, 2009)
Since the past decade, ionic liquids have gained significant importance as alternative solvents for catalysis applications. Many of the reactions evaluated in ionic liquids employ gases as substrates, and therefore it is important to know their solubility and mass transfer characteristics. This work reports for the first time both the solubility and volumetric gas-liquid mass transfer coefficient k(La) for hydrogen and carbon monoxide in 1-n-butyl-3-methylimidazolium hexafluorophosphate ([Bmim][PF6]) at three temperatures (293, 323, and 373 K) in relevance to hydroformylation reaction. The experimental data on the volumetric gas-liquid mass transfer coefficient are described by a dimensionless correlation for the bench-scale stirred tanks with gas-inducing impeller. k(La) values have also been evaluated for different [Bmim][PF6]-decane emulsions at 373 K.

Hydroformylation of 1-octene using [Bmim][PF6]-decane biphasic media and rhodium complex catalyst: thermodynamic properties and kinetic study - Sharma, Amit; Lebigue, Carine Julcour; Deshpande, Raj Madhukar; Kelkar, Ashutosh A.; Delmas, Henri (Industrial & Engineering Chemistry Research, 2010)
A chemical reaction engineering approach is reported to investigate the biphasic hydroformylation of I-octene using [bmim][PF6] ionic liquid. It is based both on a process parameter investigation (temperature, concentrations, and pressures) and a thermodynamic study of the reaction medium (gas liquid and liquid liquid equilibria). Initial rate data show complex behavior with respect to operating parameters and are best described by a rate equation based on a mechanistic model. Complete reaction scheme including isomerization is then modeled accounting from the time dependent concentration of the organic substrates measured in organic phase and recalculated in ionic liquid phase from liquid liquid equilibria.
21st International Symposium on Chemical Reaction Engineering (ISCRE 21), Philadelphia, PA, JUN 13-16, 2010

Kinetics of hydroformylation of 1-octene in ionic liquid-organic biphasic media using rhodium sulfoxantphos catalyst - Deshpande, R. M.; Kelkar, Ashutosh A.; Sharma, A.; Julcour-Lebigue, C.; Delmas, Henri (Chemical Engineering Science, 2011)
Biphasic hydroformylation of 1-octene was performed using rhodium sulfoxantphos catalyst dissolved in [BuPy][BF(4)] ionic liquid. Preliminary experiments proved this system to retain the catalytic complex within the ionic liquid phase and to maintain a high selectivity towards the linear aldehyde (n:iso ratio of 30) over several cycles. Process parameter investigation showed a first order dependence of the initial rate with respect to the catalyst and 1-octene concentrations, but a more complex behavior with respect to hydrogen (fractional order) and carbon monoxide partial pressures (inhibition at high pressures). Different mathematical models were selected based on the trends observed and evaluated for data fitting. Also, rate models were derived from a proposed mechanism, using Christiansen matrix approach. To calculate concentrations of substrates in the catalytic phase as required by this kinetic modeling, solubility measurements were preformed for the gases (pressure drop technique), as well as for 1-octene and n-nonanal (thermogravimetry analysis). (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biphasic catalysis; Butylpyridinium tetrafluoroborate; kinetics; Parameter identification; Reaction engineering; solubility